Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1182/blood.v87.5.1737.1737
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HOXC4, HOXC5, and HOXC6 in human lymphoid cell lines, leukemias, and benign and malignant lymphoid tissue

Abstract: Besides their regulatory role in embryogenesis, homeobox (HOX) genes are expressed in a specific manner in hematopoietic cell lineages, implying a role in the molecular regulation of hematopoiesis. Some HOX C cluster genes are found to be expressed in lymphoid cells of mice and humans. Their function and expression in normal hematopoiesis are still largely unknown. We have studied the mRNA expression of HOXC4, HOXC5, and HOXC6 in several stages of lymphocyte maturation by reverse transcriptase-polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…It is reported that HOXC6 participates in milk production and mammary gland development [15,16]. Moreover, aberrant expression of HOXC6 has been reported in various cancers, such as head and neck squamous cell carcinoma, gastrointestinal cancer, breast cancer, leukemia and osteosarcoma [15,[17][18][19][20]. In earlier researches, HOXC6 showed raising tendency in PCa and was involved in the cancer development [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that HOXC6 participates in milk production and mammary gland development [15,16]. Moreover, aberrant expression of HOXC6 has been reported in various cancers, such as head and neck squamous cell carcinoma, gastrointestinal cancer, breast cancer, leukemia and osteosarcoma [15,[17][18][19][20]. In earlier researches, HOXC6 showed raising tendency in PCa and was involved in the cancer development [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…RT-PCR primers and probes are listed in Table 1. As a positive and RNA quality control, RT-PCR for snRNP U1A, a low-abundance RNA transcript, was performed on all samples as described previously (Bijl et al, 1995). All samples were analysed by multi-primed RT-PCR for mRNA encoding EBNA1 (driven by the Cp, Wp or Qp promoters), LMP1, LMP2A, LMP2B and the BARTs (A3/A4), according to Brink et al (1997a).…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of HOXC4 in CD34 + cells has been shown to dramatically increase the proliferation of LTC‐IC as well as myeloid and erythroid CFCs (72). HOXC4 transcripts have been detected in CD34 + CD38 + progenitors and in terminally differentiated T and B cells (73) but not in mature granulocytes or monocytes (74). Expression of HOXC6 has been detected in mature T lineage cells, but not in CD34 + progenitors, suggesting that it functions later in lymphoid differentiation.…”
Section: Transcriptional Regulation Of Human Hematopoietic Lineage Comentioning
confidence: 99%